1991
DOI: 10.1080/03079459108418736
|View full text |Cite
|
Sign up to set email alerts
|

A trypsin‐sensitive avian reovirus: Isolation and experimental infection of poults and chicks

Abstract: A reovirus (strain TR1) was isolated from the hock joint of a turkey with arthritis. It was rarely excreted in the faeces of poults after oral or intranasal inoculation and only occasionally following footpad inoculation. The virus did not localise in the hock joints or cause lesions. Cyclophosphamide-induced immunosuppression of poults did not modify the infection. Oral inoculation of chicks with a high dose of strain TR1 resulted in joint localisation, of virus and erosive arthritis. Footpad inoculation caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Immunosuppression by this virus may also retard the success rate of vaccination against other infectious diseases such as infectious bursal disease and hepatitis [11]. ARV can be transmitted both vertically and horizontally [12]. Although ARV are not always pathogenic and have been reported from routine examination in apparently healthy poultry flocks [13].…”
Section: Introductionmentioning
confidence: 99%
“…Immunosuppression by this virus may also retard the success rate of vaccination against other infectious diseases such as infectious bursal disease and hepatitis [11]. ARV can be transmitted both vertically and horizontally [12]. Although ARV are not always pathogenic and have been reported from routine examination in apparently healthy poultry flocks [13].…”
Section: Introductionmentioning
confidence: 99%
“…The trypsin-resistant avian reovirus strain R2 and the trypsin-sensitive strain TR1 have been previously described by Al-Afaleq & Jones (1991). By cross-neutralizatio n tests in cell culture, the two viruses are antigenicall y identical.…”
Section: Virusesmentioning
confidence: 99%
“…Protection of chicks is therefore essential either by maternal immunity or early vaccination. It has recently been shown that some avian reoviruses are sensitive to trypsin and are partially inactivated in the gut (Al-Afaleq & Jones, 1991;Drastini et al, 1994) and some current vaccines have been shown to have this sensitivity (Jones et al, 1996). Such sensitive viruses replicate poorly in the intestines of chicks, even after oral infection (Jones et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The trypsin-sensitive strain TR1, originally isolated from the hock of a turkey with arthritis, has been described previously (Al-Afaleq & Jones, 1991). For some comparative infections, the trypsin-resistant strain R2 was used.…”
Section: Virusesmentioning
confidence: 99%
“…We have recently described the isolation of a strain of avian reovirus which is sensitive to trypsin (Al-Afaleq & Jones, 1991). It was found that following oral infection of chicks, virus was rarely isolated from cloacal swabs because the virus was partially inactivated by the enzyme in the intestine.…”
Section: Introductionmentioning
confidence: 99%